Classification of European bog vegetation of the Oxycocco-Sphagnetea class - Pawlikowski, Paweł; Hájek, Michal; Tokarev, Pavel N.; Šmerdová, Eva; Šímová, Anna; Plesková, Zuzana; Onyshchenko, Viktor; Lenoir, Jonathan; Košuthová, Alica; Jiroušková, Jana; Jandt, Ute; Ivchenko, Tatiana G.; et al. (Applied Vegetation Science, 2022)
25 1 Nie dotyczy